Hubungan antara Kadar LDL dan Insidensi Gagal Jantung pada Pasien dengan Infark Miokard Akut: Studi Observasional - Ghossan Faisol; Sofina Kusnadi; Joriandhita Surya Ramadhan; Erdiansyah Zulyadaini (The Indonesian Heart Association, 2026)
Background: Acute Myocardial Infarction (AMI) is one of the leading causes of cardiovascular morbidity and mortality worldwide. A serious complication that can arise from AMI is heart failure, which can significantly worsen the patient’s prognosis. LowDensity Lipoprotein (LDL) is recognized as a major risk factor for atherosclerosis and plays a critical role in the pathophysiology of AMI. This study aims to determine whether there is an association between LDL levels and the incidence of heart failure in patients with acute myocardial infarction. Methods: This observational study used medical records from Purwokerto Islamic Hospital (January 2022-December 2024) relating to patients diagnosed with acute myocardial infarction, regardless of the presence of heart failure. LDL levels were categorized as optimal or non-optimal using a cut-off level of 100 mg/dL. Bivariate analysis was performed using RStudio, while baseline characteristics that were classified by the presence or absence of heart failure status were examined with SPSS software platform. Results: Statistical analysis using the Chi-square test revealed a significant association between LDL levels and the incidence of heart failure in patients with acute myocardial infarction at Islamic Hospital Purwokerto, with a p-value of 3.52e-10/ < 0.05. Conclusion: Higher LDL levels are significantly associated with an increased risk of heart failure in AMI patients, highlighting the importance of LDL control. Further studies should consider additional factors like infarct size, myocardial injury, hypertension, diabetes, ejection fraction, and the role of inflammation for a more comprehensive risk assessment.